Pemanfaatan Limbah Gerabah Sebagai Media Tanam Alternatif Tanaman Cabai dan Tomat - Pamungkas, Tegar Putra; Sofiana, Isnaini; Wisnu Bayu Aji, Panggah; Aulia Rahman, Rifqi (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
This study analyzed the use of pottery waste as an alternative growing medium for chili and tomato plants in Tegowanuh Village, Kaloran, Temanggung. Pottery waste, which is often neglected, has the potential to improve plant growth and reduce environmental pollution. An experimental method was used to evaluate the effectiveness of pottery waste compared to conventional growing media. The results showed that chili and tomato plants grown in pottery waste media showed good growth, with higher plant height and fruit number compared to conventional soil media. In addition, the use of pottery waste contributes to the reduction of solid waste, supporting sustainable agricultural practices. The study also showed that the utilization of waste can reduce dependence on chemical fertilizers, in line with efforts to improve soil fertility. Public awareness on the importance of waste utilization in agriculture needs to be increased through training and socialization. This research is expected to be a reference for farmers and policymakers in developing more efficient and environmentally friendly agricultural practices.